POLITIK ISLAM DAN DEMOKRASI DI INDONESIA - Rasyid, Fauzan Ali (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2008)
The article is about the political movement of Islam before and after the 20th century, and its relation to the development of democracy in Indonesia. Before the 20th century, the pattern of Islam political movement was still communal in character. This social solidarity developed in social structure of agrarian society and, usually centred among charismatic leaders. The struggles against colonial government were led mostly by the local prominent figures such as in Aceh, in Central Java, and Padri War in West Sumatra. At the turn of the-20 century, the trait of Islamic movement began to change from communal form into associational and organic solidarity. Their leaders were not necessarily from local elites but they came from urban middle class. They applied modern organization practices. When in the past the relationship between the leaders and their followers was based on paternalistic type, then in the 20th century it changed in a more rational kind. The movement which was based on associational pattern made its activities expanded and left behind its former local model. In making each decision they mostly relied on democratic and deliberation ways. Hence the tradition of democracy and participation is eventually formed.